MY SAY: Hypocrisy exposed in Haiti - Abd Razak, Dzulkifli (2010)
Suddenly, Haiti is on everyone's radar screen, barely a month after the failed Copenhagen Climate Change Conference in early December last year. That also happened to be the fifth anniversary of the dreadful tsunami that hit Aceh and the countries around the Indian Ocean on Dec 26, 2004. Many see the similarities between the two tragedies, especially in terms of the number of victims as well as the seemingly sudden nature of the disaster.